The Perspective of Criminal Law Policy on Witness Protection in Corruption Eradication Case - Aris Irawan (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Corruption has become massive societal phenomenon that has been regarded as extraordinary crimes threatening Indonesian economy and impeding national development. All societal elements expect that it will not be unresolved problems. Until recently, criminal law policy in its attempt to eradicate corruption has more put emphasis on the perpetrator. Such policy on witness protection, in the criminal case of corruption, needs to be optimized because it can be an alternative legal instrument in the attempt to eradicate corruption. Law-enforcement authorities face difficulties in unfolding a corruption case because it is often well systematically planned. In many cases, witnesses are reluctant to report a corruption case because of threat, intimidation, and criminalization posed to them. Problems are (1) How is the regulation of witness protection act and the corruption eradication in Indonesia? (2) How is the urgency of witness protection in the criminal cases of corruption eradication? (3) How is criminal law policy on witness protection to facilitate the corruption eradication in Indonesia? This research employs normative juridical approach with the descriptive research type. Findings show that(1) the development of witness protection act in the corruption case is highly relate to the witness stand on the criminal justice system; (2) the urgency of witness protection in the corruption eradication process is highly related to the common occurrence of intimidation and threat toward the witnesses. It indicate that the witness and victim protection is an important and urgent legal aspect; (3) criminal law policy in the corruption eradication process put more emphasis on the perpetrators and less concern on the witnesses involved in legal investigation. It is necessary to optimize the role of LPSK in criminal law policy including in giving the protection to witness in the case of corruption eradication; therefore, it is important to conduct legal update on the witness protection act in the case of corruption eradication process.